1977
DOI: 10.1002/ar.1091880106
|View full text |Cite
|
Sign up to set email alerts
|

The vertebral level of origin of spinal nerves in the rat

Abstract: Several dissections were performed to determine the level of spinal cord termination and the vertebral level at which the dorsal and ventral roots of spinal nerves C1-S4 emerged from the spinal cord in the rat. These levels of emergence were then compared to the level of exit from the vertebral canal. The dissections demonstrated that the effect of differential growth between spinal cord and vertebral column begins in the lower cervical region and becomes progressively more pronounced throughout thoracic and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
4

Year Published

1979
1979
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 0 publications
0
44
0
4
Order By: Relevance
“…S1). This finding demonstrates that ganglionar administration does not reach the spinal cord, and was limited to the primary afferent neurons because secondary afferent neurons from L5-DRG are located at the L1-T13 spinal cord segment (18).…”
Section: Resultsmentioning
confidence: 84%
“…S1). This finding demonstrates that ganglionar administration does not reach the spinal cord, and was limited to the primary afferent neurons because secondary afferent neurons from L5-DRG are located at the L1-T13 spinal cord segment (18).…”
Section: Resultsmentioning
confidence: 84%
“…In the rat, the spinal cord terminates at L3-L4 vertebral level, whereas in the human it terminates at L1-L2 vertebral level. 24 It is unknown whether there are functional differences between the intrathecal space and flow of cerebrospinal fluid between rats and humans. Figure 4 Relative distribution of NSPC (a) and BMSC (b) in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…Zeman and Inne [1963] show that the spinal nerve roots lie slightly cranial to their level of exit and the cord terminates between the third and fourth lumbar vertebrae. Gelderd and Chopin [1977] have observed that the spinal nerve roots in rat arise considerably rostral to their level of exit. The present investigation was therefore under taken to clarify these discrepancies.…”
Section: Introductionmentioning
confidence: 98%